Optimalisasi Pembelajaran Berbasis Outdoor Learning dalam Meningkatkan Minat Belajar Siswa SD Negeri 15 Langkan - Marni R., Santi; Ernawati, Ernawati; Aminah, Siti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to optimize outdoor learning-based instruction to enhance students’ learning interest at SD Negeri 15 Langkan. The research employs Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of planning, action, observation, and reflection in two cycles. The subjects are fifth-grade students who demonstrate low learning interest in conventional classroom instruction. Data were collected through observations, interviews, learning interest questionnaires, and documentation. The findings indicate that implementing outdoor learning significantly increases students’ learning interest. In the first cycle, learning interest increased by 15%, and in the second cycle, it improved by 30%. Outdoor learning provides a more engaging and contextual learning experience, making students more enthusiastic and active in the learning process. The study concludes that outdoor learning can be an effective strategy to enhance elementary school students’ learning interest.